Perdas de água e variações na temperatura de um argissolo vermelho em função de diferentes quantidades de resíduos vegetais na superfície e espaçamentos entre linhas do feijoeiro - Oliveira, Zanandra Boff de (2011)
Irrigation is an alternative to minimize fluctuations in grain production and yield due to water deficiency. However, to prevent water losses and to improve the efficiency of this use, the irrigation management has to be sustainable. Therefore, the knowledge of the number of variables related with soil and crops, in response to different growing conditions is fundamental to have an adequate irrigation management. Thus, tere objective of tail study was made to evaluate water losses, variations in the soil temperature with different spacing between rows and the amount of plant residues on the surface of the soil during the cultivation of beans. This experiment was conducted in the experimental area of the Agricultural Engineering Department at the Federal University of Santa Maria, in 2010, under a rainout shelter. The experimental design was completely randomized bi-factorial with three replications. Factor A was consisted of three spacing rows between crops: 30, 50 and 70 cm. Factor B was consisted of two quantities of crop residues on soil surface: 1 Mg ha-1 of corn residues and 5 Mg ha-1 of corn + oat residues. The water content in the soil was determined by a FDR set (Frequency domain reflectometry, Campbell Scientific), in layers of the soil profile: 0-10, 10-25, 25-55 and 55-85 cm deep. Daily water storage in the soil (mm), daily and accumulated water losses in soil (mm) were evaluated. Soil temperature was mensured ussing thermocouples made of copper and constantan were installed at the depths of 3, 8, 15 and 35 cm. Morphological determination were conducted of the dry beans plants (leaf area and plant height) and the determination of the coverage fraction of the plants between the rows. The dry beans plants were 7cm higher in the plot with 5 Mg ha-1 of corn + oat residues on the surface. The full coverage of the dry beans plants between rows occurred primarily in the spacing of 30 cm at 47 days after sowing, and the spacing of 50 and 70 cm occurred at 61 days after sowing with a maximum leaf area index 6,8. Accumulated soil water losses during the development cycle of the dry beans, in the different layers of the soil profile down to 85 cm deep, were not affected by row spacing of cultivation from 30 to 70 cm. In the early stage of development of the dry beans plants, considering the period of 30 days after sowing, (104 mm of reference evapotranspiration accumulated) in the layer of the soil profile from 0-10 cm deep, using 5 Mg ha-1 of corn + oat residues on the soil surface reduced 26% of water losses in the soil, resulting in a better water storage and availability to plants. Using 5 Mg ha-1 of corn + oats residues on the soil surface caused reductions in soil temperature (minimum and maximum) up to 3oC. The soil temperature (minimum and maximum) increased linearly with the spacing between rows from 30 to 70 cm. The average values of yield components and yield of the beans of the treatments were 18 pods plant-1, 6 grains pod-1 and 3, 45 Mg ha-1.